Self-Injury Among Left-Behind Adolescents in Rural China: The Role of Parental Migration and Parent–Child Attachment - Wang, Yulong; Zhang, Manqi; Chen, Huiling (Frontiers in Psychology, 2019)
Previous studies have indicated that self-injury is a maladaptive coping strategy with a high incidence among left-behind adolescents in rural China. However, few studies have been conducted on the factors influencing left-behind adolescents’ self-injury. The current study explored the roles of parental migration and parent–child attachment on self-injury. In total, 1110 adolescents were selected from 4 rural middle schools in Hunan province. Data on demographic and left-behind characteristics were collected and the Adolescent Self-Harm Scale and Inventory of Parent and Peer Attachment were administered. The results indicated that compared with non-left-behind children and children with one parent migrating, there was a higher incidence of self-injury among children with two parents migrating. Those with lower levels of parent–child attachment had a higher incidence of self-injury than those with higher levels of parent–child attachment. There were also significant differences in terms of frequency, severity, and overall level of self-injurious behavior by patterns of parental migration and levels of parent–child attachment. Thus, parental migration, parent–child attachment, and the interaction between parental migration and mother–child attachment can predict adolescents’ self-injury.